2002
DOI: 10.1097/00007632-200207010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Combined Magnetic Fields Accelerate and Increase Spine Fusion

Abstract: In conclusion, the adjunctive use of the combined magnetic field device was statistically beneficial in the overall patient population, as has been shown in previous studies of adjunctive bone growth stimulation for spine fusion. For the first time, stratification of fusion success data by gender demonstrated that the female study population responded positively to the adjunctive combined magnetic field treatment, with no statistically significant effect observed in the male study population. Adjunctive use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Three studies compared DC stimulation to no stimulation,8 9 10 with only one study using a placebo device (i.e., an inactive stimulator) in the control group; three compared PEMF stimulation to no stimulation,9 11 12 with two employing placebo devices, and one study compared CC to no stimulation using placebo devices 13. Marked heterogeneity was present across the studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared DC stimulation to no stimulation,8 9 10 with only one study using a placebo device (i.e., an inactive stimulator) in the control group; three compared PEMF stimulation to no stimulation,9 11 12 with two employing placebo devices, and one study compared CC to no stimulation using placebo devices 13. Marked heterogeneity was present across the studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…35 Studies using simple static radiography, 2,3,23 dynamic radiography, 36 computed tomography, 23,30 and clinical criteria, in particular the complaint of pain, 2 were found in the literature. In addition to the variety of methods, the interpretation of the results is occasionally subjective and has low reproducibility.…”
Section: Effect Of Pulsed Electromagnetic Field On the Consolidation mentioning
confidence: 99%
“…In animal models, increased mineral bone density, 51 increased bone stiffness, 22,52 and more rapid incorporation of bone grafts were observed with the use of PEMF, but no significant improvement was found in the final consolidation rate. 21,23 In a prospective, double-blind, randomized clinical study, Mooney 50 observed a bone consolidation rate of 92% in interbody lumbar arthrodesis surgeries with the use of PEMF versus 65% in the control group. Bose 3 found a consolidation rate of 97.9% after posterolateral lumbar arthrodesis, but the study was performed without a control group.…”
Section: Effect Of Pulsed Electromagnetic Field On the Consolidation mentioning
confidence: 99%
See 1 more Smart Citation
“…Generation and accurate control of such fields within the human body is a relatively easy matter and is routinely done for diagnostic purposes [16], with fields as high as several Tesla commonly being employed. Furthermore, application of a static magnetic field has already been proposed [17,18] as a means of stimulating bone growth, although the effects are not yet entirely clear and the bio-chemical mechanisms involved remain to be fully identified. In the present paper, the novel suggestion is put forward that bone growth could be stimulated in vivo via a magnetomechanical mechanism involving the transmission of stresses and strains to growing bone via small local deflections within a porous ferromagnetic material, induced by the application of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%